Copper removal using ion exchanger flat sheet mixed matrix membrane : effect of polyethersulfone composition on membrane properties - Fong Fong, Kiew (2015)
Ion exchanger has been widely used and applied in removal of heavy metal in wastewater treatment. In the current study, mixed matrix membrane (MMM) ion exchanger was developed by incorporating Amberlite IR120H into polyethersulfone (PES) dope polymer solution for copper removal. The effect of PES composition in dope polymer solution was varied from 23wt%, 25wt%, 28wt% and 30wt% at constant amount of 20g Amberlite IR120. The performance of membrane was evaluated using batch binding and cross flow filtration. In batch binding, the highest static binding capacity of the copper removal was achieved by membrane prepared from 30wt% PES with the binding efficiency at a value of 64% from 500ppm standard solution of copper (II) sulphate pentahydrate. In cross flow filtration, 30wt% PES membrane has the maximum binding efficiency at 95%. Regeneration study was studied with 30w%t PES membrane using 10%HCL elution solution in three consecutives running cycle. The membrane can be regenerated with 97% binding efficiency in each 3 cycles meaning all the membrane produced can be regenerated. As a conclusion, the higher the composition of PES membrane, the higher the adsorptive performance, thus 30wt% PES membrane was the optimum PES composition.